Identification and Evaluation of Non-Accidental Trauma in the Pediatric Population: A Clinical Review - Sophia M. V. Schermerhorn; Oliver J. Muensterer; Romeo C. Ignacio (MDPI AG, 2024)
Non-accidental trauma (NAT) is a major cause of morbidity and mortality for children around the world and most significantly impacts children under one year of age. Prompt and comprehensive treatment of these children relies on a high index of suspicion from any medical provider that treats pediatric patients. This review discusses those most at risk for experiencing NAT, and common initial presentations, to assist providers in the identification of potential victims. In addition, this review provides guidance on the recommended workup for these patients so that the full extent of associated injuries may be identified and the appropriate healthcare team may be assembled.